Development of YouTube-Based Electrolysis Learning Media to Increase Student Learning Motivation - Ghaitsa Zahira Shofa Pradana Putri; Hayuni Retno Widarti (Jurnal Penelitian Pendidikan IPA, 2025)
The low motivation of students in learning chemistry, especially electrolysis, encourages educators to continue to develop new innovations in the learning process that are tailored to the characteristics and needs of students. This research aims to develop YouTube-based electrolysis learning media to increase student learning motivation. The method used is Research and Development (R&D) with the ADDIE development model until the development stage. Preliminary tests carried out include validity tests, readability tests, and small-scale trials. The developed media was tested in problem-based learning using a one-group pretest-posttest design to assess the effectiveness of the developed media in increasing student learning motivation. Quantitative data obtained from a Likert scale (5, 4, 3, 2, 1) was analyzed using the average percentage calculation technique for validation tests and student perspective tests, as well as standard gain for small-scale trial data. The data obtained were then interpreted into categories of feasibility and improvement, followed by revision based on suggestions from qualitative data. The research results in the form of a YouTube social media account named “YuroLab” with three educational video content. The validation test resulted in an average score of 83.89%, and the student perspective test resulted in a score of 81.99%, placing it in the very feasible category. The increase in student learning motivation resulted in an average standard gain of 0.58 which is included in the moderate category.